Consumer Purchase Decision Making Behavior of Fashion Products on Shopee in Surabaya City - Viona Rosalinda Dwi Putri; Tri Kartika Pertiwi; Nanik Haryana (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the role of consumer trust in mediating the effects of affiliate marketing and online customer ratings on purchase decisions for fashion products among Shopee users in Surabaya. A quantitative approach was used in this research, with data collected through questionnaires from 100 Shopee users in Surabaya. The data analysis was conducted using the Partial Least Squares (PLS) method to examine the direct and mediating relationships between the variables: affiliate marketing, online customer ratings, consumer trust, and purchase decisions. Validity and reliability tests of the instruments were also performed to ensure the accuracy of the variable measurements in this research model.The findings indicate that affiliate marketing does not significantly drive consumer purchase decisions. However, consumer trust plays a key role in mediating the relationship between affiliate marketing and purchase decisions. Without trust, affiliate marketing promotions have limited influence. Additionally, online customer ratings positively influence purchase decisions, and consumer trust is crucial in mediating the relationship between online customer ratings and purchase decisions. Positive ratings from other customers enhance trust in both the product and the seller.